3D-printed model combined with the Ilizarov technique in the treatment of genu varum in children with hypophosphatemic rickets - Shu Chen; Bin Gao; Qiang Shi (Journal of Orthopaedic Surgery and Research)
Abstract Introduction Genu varum in children with hypophosphatemic rickets are complex and always occur on multiple planes, which are difficult to correct. This present study is aimed to retrospectively explore the feasibility and efficacy of 3D-printed model combined with the Ilizarov technique in the treatment of genu varum in children with hypophosphatemic rickets. Methods From March 2010 to July 2020, 7 hypophosphatemic rickets patients with genu varum were retrospectively analyzed in our hospital. Under the assistance of 3D-printed model, all of them were performed double-level osteotomies successfully with Ilizarov fixation. There were 3 boys and 4 girls. All patients had abnormal alignment of their lower limbs, with 14 limbs having genu varum deformity. The age of patients when they obtaining the corrective surgery averaged 7 years with a range of 5–10 years. Results All patients were followed up for a period of 29–95 months, with an average of 44.5 months. Bony union was achieved for 5 to 10 months (average 6.9 months) after double-level osteotomies. During the last follow-up, no complaints of pain, no restriction of motion of the knee joints, or recurrence was found. The average preoperative mLDFA was 98.8 degrees (89–113 degrees), and the average mLDFA at the final follow-up was 93.4 degrees (85–101 degrees). Meanwhile, the MPTA improved significantly from 83.6 degrees (74–88 degrees) to 86.7 degrees (78–90 degrees), as well as the MAD from 65.7 mm medial (62–71 mm) to 18.5 mm medial (14–21 mm). Conclusion For genu varum in children with hypophosphatemic rickets, double-level osteotomies and Ilizarov fixation with the aid of 3D-printed model can achieve promising clinical and radiological outcomes with few complications.